Treatment of oligometastatic lung cancer with brain metastases using stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT). (March 2020) - Nikitas, John; Roach, Michael; Robinson, Cliff; Bradley, Jeffrey; Huang, Jiayi; Perkins, Stephanie; Tsien, Christina; Abraham, Christopher
Highlights: Stereotactic radiation was used for both lung cancer primaries and brain metastases. Oligometastatic and stage I patients achieved similar survival and local control. Both patient groups had low toxicity rates. Local radiation alone is effective and safe for oligometastatic lung cancer. Abstract: Background: There is increasing interest in treating oligometastatic non-small cell lung cancer (NSCLC) patients with stereotactic radiation. We aimed to address whether patients definitively treated with synchronous thoracic stereotactic body radiation therapy (SBRT) and brain stereotactic radiosurgery (SRS) had favorable outcomes with local therapy. Materials and methods: We reviewed a database of patients receiving lung SBRT as well as a database for brain metastasis patients treated with SRS between June 2004 and January 2016. We selected for cT1-2aN0M1 NSCLC patients with brain metastases and calculated their overall survival (OS), freedom from progression (FFP), and local control (LC) rates. Results: Six patients had oligometastatic NSCLC with 1–3 synchronous brain metastases treated with lung SBRT and brain SRS. No patients received immunotherapy and two-thirds did not receive systemic therapy. Median follow-up was 9 months for the entire cohort (range, 2–95 months) and 95 months for the surviving patient. Median OS was 12.4 months (95% confidence interval [CI], 7–18 months). At 1 year, patients had 67% OS (95% CI, 29–100%), 17% FFP (95% CI, 0–46%), and 100% LC. Their brain disease had 80% 1-year LC (95% CI, 45–100%) and 53% 1-year FFP (95% CI, 5–100%). Two patients had no distant progression, two had brain progression, one had adrenal gland progression, and one had bone and liver progression. Conclusion: In patients presenting with oligometastatic lung cancer limited to the brain, treatment with both lung SBRT and brain SRS achieves good LC of all sites with encouraging OS.